Fine needle aspiration cytology of thyroid and its correlation with serological findings (Journal of Pathology of Nepal, 2017)
Background: Thyroid autoimmunity can cause several forms of thyroid disorders i.e. Grave’s disease, Hashimoto’s thyroiditis, atrophic autoimmune thyroiditis, post-partum thyroidits etc. Cytological diagnosis may be sometimes difficult is some cases. In such conditions, cytology along with serological tests aid at reaching a correct diagnosis.Hence, this study was undertaken to evaluate the serum level of anti-TPO antibody with respect to serum concentrations of thyroid hormones and its importance in diagnosing autoimmune thyroiditis.Material and Methods: This study was carried out in the department of pathology from June 2013-May 2014. Patients coming to the department of pathology TUTH, Maharajgunj for FNA of thyroid were included. TFT level was noted and anti TPO antibody level was evaluated by CLIA.Results: Ninety-five thyroid FNAC was included in the study, which comprises of 16.8 % males and 83.2% females with a M: F 1: 4.9. Maximum number of cases was seen in the age range 21-30 years (25.3%), mean age being 40.4years. The cytological diagnosis comprised colloid goiter(43.2%), lymphocytic thyroiditis (25.3%), Hashimoto thyroiditis(18.9%). Out of 42 cases of autoimmune thyroiditis diagnosed cytologically, 16 (38%) were hypothyroid, 4 (9.5%) hyperthyroid, 8 (19%) sub-clinical hypothyroid and 14 (33.5%) were euthyroid. The sensitivity and specificity of positive anti TPO in correctly identifying autoimmune thyroiditis was 85.7% and 79.2% respectively. The positive and negative predictive value for the test was 76.5% and 87.5% respectively.Conclusion: Nodular goitre can harbour a certain per cent of autoimmune thyroiditis and in such cases anti TPO antibody level along with cytodiagnosis appears to be helpful.